1999
DOI: 10.1073/pnas.96.23.13369
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibition of tumor survivalin vivoby β-lapachone plus taxol: Combining drugs imposes different artificial checkpoints

Abstract: Ablation of tumor colonies was seen in a wide spectrum of human carcinoma cells in culture after treatment with the combination of ␤-lapachone and taxol, two low molecular mass compounds. They synergistically induced death of cultured ovarian, breast, prostate, melanoma, lung, colon, and pancreatic cancer cells. This synergism is schedule dependent; namely, taxol must be added either simultaneously or after ␤-lapachone. This combination therapy has unusually potent antitumor activity against human ovarian and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
133
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 23 publications
4
133
0
1
Order By: Relevance
“…[17][18][19][20][21][22] We subsequently confirmed that growth inhibition was mediated, at least in part, by induction of apoptosis, as indicated by increased caspase 3/7 activity and intranucleosomal fragmentation. In addition, beta-lapachone-treated Y79 RB cells displayed cellular morphology characteristic of apoptosis, including chromatin condensation, nuclear fragmentation with bleb formation, and pyknotic bodies 28 (http:// www.cyto.purdue.edu/cdroms/flow/vol4/index.htm).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…[17][18][19][20][21][22] We subsequently confirmed that growth inhibition was mediated, at least in part, by induction of apoptosis, as indicated by increased caspase 3/7 activity and intranucleosomal fragmentation. In addition, beta-lapachone-treated Y79 RB cells displayed cellular morphology characteristic of apoptosis, including chromatin condensation, nuclear fragmentation with bleb formation, and pyknotic bodies 28 (http:// www.cyto.purdue.edu/cdroms/flow/vol4/index.htm).…”
Section: Discussionmentioning
confidence: 71%
“…27,34,35 Although our experiments were limited to evaluating the cytotoxic effects of beta-lapachone alone in RB cells, a number of studies have found significant synergistic effects of beta-lapachone with other chemotherapeutic agents. 18,[35][36][37] Beta-lapachone induces G1/S checkpoint delay before inducing cell death, and remarkable in vitro and in vivo synergistic effects have been observed when this agent is administered in combination with taxol, which arrests cells in G2/M. 18 Beta-lapachone has also been reported to enhance the cytotoxicity of alkylating agents in vitro, possibly owing to beta-lapachone-induced inhibition of DNA repair.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations